Effect of Substituting Coconut Milk with Palm Milk on Shelf Life, Physicochemical and Sensory Properties of Nasi Dagang - Zulkifli, Nur Afiqah; Othman, Azizah; Seow, Lay Jing; Seow, Eng Keng (Department of Technology of Agricultural product (THP) Jambi University, 2024)
A popular Malaysian dish called Nasi Dagang (ND), which originated in Terengganu, consists of steamed rice in coconut milk (CM), fish curry, and additional ingredients such as pickled cucumber and carrots. However, CM with high saturated fat content is always associated with many diseases due to the increased amount of high-density lipoprotein cholesterol. Thus, palm milk (PM) at various concentrations (ND0 with 100% CM, ND1 substituted with 25% PM, ND2 substituted with 50% PM, ND3 substituted with 75% PM and ND4 substituted with 100% PM) were investigated in the present study to examine its effect on the physicochemical and sensory characteristics of ND. Substitution of PM in ND demonstrated an apparent effect on its nutritional value, shelf life, and quality, as evidenced by a greater calcium (4.51 ppm), carbohydrates (16.51%), and lesser fat (5.93%) contents in ND4 than that of ND0. This study discovered that although ND with PM substitution took a longer time to retrograde and turn rancid, the rising moisture content fostered the growth of microorganisms. According to this study, ND prepared with PM has a softer texture since it contains less amylose content (0.37%). Next, sensory acceptability analysis demonstrated that ND1 obtained a higher score than other ND for all aspects, including overall acceptance (7.24). The results showed that substitution of PM in ND had a strong influence on its nutritional value, shelf life, and sensory acceptability. Hence, it can be concluded that PM has a potential to replace CM in ND with certain amount of concentration.